DIFFUSION OF A QUALITY MANAGEMENT SYSTEM: A CASE STUDY - Solomon, Noel Phillip; Bester, Andre; Moll, C M (The South African Journal of Industrial Engineering, 2017)
The diffusion of a quality management system (QMS) to improve business performance depends upon the quality management strategy used. The aim of Eskom’s QMS strategy was to create a sustainable quality drive throughout the company to improve customer and stakeholder satisfaction. This research project’s objective is to determine how the diffusion of a QMS can improve the electricity supply industry in the Western Cape division of the electricity sector in South Africa. A quantitative research methodology was employed in the study. The responses to a survey questionnaire were analysed and conclusions were drawn. The research finding is that diffusion of a QMS improves the electricity industry by positively affecting attitudes towards the challenge of securing a sustainable long-term energy supply; improving processes and practices; engendering a quality culture; and contributing towards continual improvement. At the same time, certain barriers to the implementation of a sustainable QMS were identified.